PENERAPAN MODEL PEMBELAJARAN LANGSUNG UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS I SDN 006 TRI MULYA JAYA - Tukirah Kurniasih (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2017)
The background of this study is the low student learning outcomes IPA. Of the 20 students who completed only 9 students and the average student learning outcomes of 62. The results of student learning is still below the specified KKM is 65. The purpose of this research is to improve the learning outcomes of the first grade science students at SDN 006 Tri Mulya Jaya. This research is a class act, carried out by two cycles. This research was conducted by applying direct instructional model. The data used in this research is data teacher and student activities and student learning outcomes IPA. Research suggests that the application of the model pembelajara direct positive impact, namely by increasing the activity data and the results of teachers and students learn science. In the first cycle of the first meeting activity for teachers to get a percentage of 37.00%, in the first cycle II meeting increased with the percentage of 50.00%, in the first meeting silus II teacher activity increased with the percentage of 74.00% and the second cycle of meeting II increases with the percentage of 82.00%. Besides the student activity also increased, in the first cycle of meetings I earn a percentage of 37.00%, in the first cycle II meeting increased with the percentage of 41.00%, in the first meeting silus II student activity increased with the percentage of 76.00 % and the second cycle II meeting increased with a percentage of 80.00%. IPA learning outcomes of students also increased in the first cycle the number of students who completed study results berjuumlah 14 (70.00%), and the second cycle the number of students who have increased the number of students 17 (85.00%). Similarly, the average value obtained in the classical student at baseline was only 62, and after the first cycle increased by an average of 72.5 after the second cycle is increased to an average of 76.5.